The hydric stress influence on quantityand quality of the maize yield in the Crisurilor Plainconditions - Domuţa, Cristian (Acta Agraria Debreceniensis, 2013)
The paper is based on the researches carried out in an experiment placed on the preluvosoil from Agricultural Research and Development Station Oradea, Crisurilor Plain during 2008–2011in the following variants: V1=Irrigated, without irrigation suspending; V2=Irrigated, irrigation suspending in May; V3=Irrigated, irrigation suspending in June; V4=Irrigated, irrigation suspending in July; V5=Irrigated, irrigation suspending in August; V6=Unirrigated. The hybrid used: Fundulea 376. In the variant with optimum irrigation, water reserve on 0–75 cm depth was maintained between easily available water content and field capacity. Pedological drought was determined every year and the irrigation was also needed. The irrigation determined the increase of the total water consumption and yield gain in comparison with unirrigated variant. Irrigation suspending in different months determined the yield losses very significant statistically. The biggest protein content was registered in the variant without irrigation suspending; the values registered in the variants with irrigation suspending in May, June, July and August and in the unirrigated variant are smaller, with differences statistically assured. There was a direct link between de Martonne aridity index values and water consumption, yield and protein content and an inverse link between pedological drought and yield quantity and protein content. These are the arguments for irrigation opportunity in maize from Criurilor Plain.